"You are not our only child": Neoliberalism, food security issues and CSR discourse in the Kutubu oilfields of Papua New Guinea. (March 2015) - Imbun, Benedict Y.; Duarte, Fernanda; Smith, Paul
Abstract: This paper examines neoliberalism coupled with corporate social responsibility (CSR) endeavours in the context of international extractive companies and their implications on the psyche and livelihoods of rural people of developing countries. The inevitability of international capital with neoliberal ideals imposing on sometimes unsuspecting rural social and environmental landscapes of developing countries has become real in recent decades. While international capital is discriminative in its accumulative role via the placating role of CSR in such countries, the hosts, including the governments, sometimes continue to largely miscomprehend the implications of their absorption into a dominant global economy. The paper addresses some of the poignant points of local community livelihood struggles whilst discussing the Lake Kutubu villagers as they host an oil company in their pristine backyards in Papua New Guinea (PNG). The company׳s strategies of CSR and community 'empowerment' in the form of a food security programme are critically examined to highlight inherent contradictions embedded in a globalised extractive industry. Highlights: We argue that neoliberalism values and nuances in the form of CSR are spread by multi-national extractive companies. We examine the profound social and economic changes brought by an extractive company in an isolated community in PNG. Though the local communities are powerless, they seemed to have collective power. Increased mobilisation of voice has led to raising the issue of food security in the yards. The intervention in the food security programmes by the extractive companyis a result of the collective power of the local community.